Psychological well-being and coping strategies of the forcefully displaced Rohingya refugees (Dhaka University Journal of Biological Sciences, 2023)
Despite the immensity and severity of the Rohingya refugee crisis, information on their psychological well-being and coping mechanisms are limited. This work aims to synthesize research on the mental health and coping strategies of Rohingya refugees. Forty-four purposely sampled refugees completed a cross-sectional survey in the form of a structured interview, providing demographic information as well as responses on the Bangla Psychological well-being measure and the Bangla coping scale. The mean score for respondents' psychological well-being was 246.9 (SD = 25.39), while the mean score for adaptive coping was 35.93 (SD = 4.64) and the mean score for nonadaptive coping was 26.29 (SD = 3.76). Results showed a statistically significant difference (t= -2.185, p